Facilitating interprofessional affective learning in health professional students through digital client documentation: a comparison of simulation modes. Issue 6 (2nd November 2022) - Randall, Christine; Johns, Lise; Mey, Amary; Parker-Tomlin, Michelle; Reeves, Nathan; Chan, Pit Cheng; Cardell, Elizabeth; Bialocerkowski, Andrea; Rogers, Gary D.
ABSTRACT: Digital Interprofessional Learning Client Documentation (D-IPL Client Docs) is an initiative designed to develop student interprofessional communication skills through electronic record writing and a virtual simulation (VS) or live virtual simulation (LVS) case conference. The aims of the study were to (a) identify whether D-IPL Client Docs supports student learning in the affective domain and (b) compare the learning outcomes for students participating in the VS versus the LVS case conference. Data were drawn from 83 Bachelor of Social Work students who had participated with other health professional students in the D-IPL Client Docs activities. The reflective journals submitted by this cohort of social work students were analyzed qualitatively and quantitatively using the Griffith University Affective Learning Scale. Qualitative analyses revealed that the activities enabled students in both groups to learn about themselves, their roles, and the roles of others, and the benefits of interprofessional collaboration in optimizing client outcomes. Quantitatively, the VS mode appeared to be more effective in supporting students to develop higher order affective learning; however, the effect size was small. Future studies should involve a larger sample size and include students from various professions to ascertain the transferability of findings.